2010
DOI: 10.1002/mds.23059
|View full text |Cite
|
Sign up to set email alerts
|

The grasp reflex: A symptom in need of treatment

Abstract: The grasp reflex is one of the primitive reflexes frequently observed in neurodegenerative diseases. However, quality of life and treatment of the grasp reflex are neglected in the literature. Following two brief case vignettes of patients seen recently who experienced disability from a grasp reflex, we briefly review its phenomenology, anatomy-physiology and epidemiology in neurodegenerative movement disorders, and assess the limited current literature regarding the quality of life and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Presumably, these reflexes disappear because of development of the brain and descending systems. Grasp reflexes emerge in adults with structural brain (Walshe and Hunt, 1936) and neurodegenerative diseases and their pathological reemergence can be quite disabling for both hand (Mestre and Lang, 2010) and foot function (Paulson and Gottlieb, 1968). In addition, the opposite effect – loss of normal control of hand grasp such as seen after spinal cord injury – is significantly disabling (Anderson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, these reflexes disappear because of development of the brain and descending systems. Grasp reflexes emerge in adults with structural brain (Walshe and Hunt, 1936) and neurodegenerative diseases and their pathological reemergence can be quite disabling for both hand (Mestre and Lang, 2010) and foot function (Paulson and Gottlieb, 1968). In addition, the opposite effect – loss of normal control of hand grasp such as seen after spinal cord injury – is significantly disabling (Anderson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Grasp reflex is a frontal release sign and represents a rather rare catatonia sign, but often occurs in neurodegenerative disorders [40,41]. In their large heterogeneous catatonia sample, Wilson et al 2015 [42] reported a grasp reflex in only 14 % of the patients with confirmed catatonia.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to suggest the grasp reflex as a predictor of late response to ECT in the treatment of catatonia. Grasp reflex is a frontal release sign and represents a rather rare catatonia sign, but often occurs in neurodegenerative disorders 40 41 . In their large heterogeneous catatonia sample, Wilson et al 2015 42 reported a grasp reflex in only 14% of the patients with confirmed catatonia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, dI3 INs mediate a palmar grasp reflex at early postnatal stages (Bui et al 2013) that resembles a postnatal grasp reflex in humans. This reflex disappears in time (Mestre and Lang 2010), in parallel with the maturation of descending pathways to the spinal cord (Clarac et al 2004). In addition, abnormal grasp reflexes in human patients have often been associated with frontal cerebral lesions (Mestre and Lang 2010), perhaps due to loss of supraspinal regulation of dI3 INs or of an analogous population in humans.…”
Section: Connecting Spinal Circuits With Supraspinal Circuits For Sensorimotor Integration Of Tactile Informationmentioning
confidence: 94%
“…This reflex disappears in time (Mestre and Lang 2010), in parallel with the maturation of descending pathways to the spinal cord (Clarac et al 2004). In addition, abnormal grasp reflexes in human patients have often been associated with frontal cerebral lesions (Mestre and Lang 2010), perhaps due to loss of supraspinal regulation of dI3 INs or of an analogous population in humans. Supraspinal regions may also be targeted by dI3 INs, as revealed by their innervation of the lateral reticular nucleus, a precerebellar nuclei (Pivetta et al 2014).…”
Section: Connecting Spinal Circuits With Supraspinal Circuits For Sensorimotor Integration Of Tactile Informationmentioning
confidence: 94%